Analysis of mechanics around a localised surface defect of cylindrical roller bearing. (June 2019) - Tang, Haohui; Liu, Heng; Zhao, Yang; Tian, Guibin; Xu, Zhidong
In the paper, in order to investigate the mechanics around a localised surface defect of cylindrical roller bearing, a dynamic model is built based on the model proposed by Gupta to calculate the carrying loads of rollers when the rollers pass over the defect zone under different circumstances. A defect model is built by the finite element method to calculate the stress distribution around the defect. Three stages are defined to simplify the analysis of mechanics in this process. With the increase of the rotor speed, the stress received by the exit edge increases. The increase of the radial load or defect length leads to the increase of stresses in all stages. When the defect position deviate from the centre line and is close to the edge, the stress received by the exit edge on the surface increases but the sizes of stress on the subsurface decrease.